Comparison of different test configurations for the shear fracture toughness evaluation of a ductile adhesive - Leal, A.J.S. (2020)
Cohesive zone modelling (CZM) is widely used for predicting the strength of adhesive joints. The key variable for crack path modelling is the critical strain energy release rate (GC), which can be separated into the tensile (GIC) and shear (GIIC) components. In shear, the End Notched Flexure (ENF) test is widespread. However, other test methods exist and could be a viable replacement. This work aims to make a numerical evaluation between the ENF and Four-Point End Notched Flexure (4ENF) tests to determine GIIC of a ductile adhesive (SikaForce® 7752) and to provide shear CZM laws for further application in design. An inverse technique was used to obtain the shear CZM laws of the adhesive. It was concluded that the GIIC values obtained by the ENF and 4ENF tests are in good agreement. The numerical analysis led to unique shear CZM laws for both tests, with similar results.